Family-based home care assistance for children at risk of stunting through nutrition interventions and healthy parenting - Sitti Zakiyyah Putri; Indrawati Aris Tyarini; Herlianty Herlianty; Mira Kohmala Bauw; Andi Mukarramah (Edukasi Ilmiah Indonesia, 2026)
Stunting remains a major public health challenge that threatens child growth and long-term human development, particularly among vulnerable families. Family-based interventions are essential to address the behavioral and environmental determinants of stunting that occur at the household level. This community service program aimed to strengthen family capacity in preventing stunting among children at risk through family-based home care assistance focusing on nutrition interventions and healthy parenting practices. The program was implemented using a structured and participatory approach consisting of five stages: socialization, training, application of appropriate technology, mentoring and evaluation, and program sustainability. Activities were conducted with families who had children at risk of stunting and were supported by community nurses and health cadres. Training emphasized balanced nutrition, age-appropriate feeding practices, dietary diversity using locally available foods, hygiene and sanitation, healthy parenting, and child growth monitoring. Simple digital educational media and mobile-based communication were used to reinforce learning and facilitate follow-up. Mentoring was carried out through regular home visits to provide individualized guidance and support behavior change. The results showed improvements in caregiver knowledge, feeding practices, healthy parenting behaviors, compliance with child growth monitoring, and utilization of simple technology after program implementation. These findings indicate that family-based home care assistance is a feasible and effective approach to strengthening family capacity for stunting prevention. Integrating nutrition education, healthy parenting support, appropriate technology, and continuous mentoring within community-based services can contribute to sustainable improvements in child nutrition practices and support long-term efforts to reduce stunting at the community level.